Interseismic Slip and Coupling along the Haiyuan Fault Zone Constrained by InSAR and GPS Measurements - Xin Qiao; Chunyan Qu; Xinjian Shan; Dezheng Zhao; Lian Liu (Remote Sensing, 2021)
The Haiyuan fault zone is an important tectonic boundary and strong seismic activity belt in northeastern Tibet, but no major earthquake has occurred in the past ∼100 years, since the Haiyuan M8.5 event in 1920. The current state of strain accumulation and seismic potential along the fault zone have attracted significant attention. In this study, we obtained the interseismic deformation field along the Haiyuan fault zone using Envisat/ASAR data in the period 2003–2010, and inverted fault kinematic parameters including the long-term slip rate, locking degree and slip deficit distribution based on InSAR and GPS individually and jointly. The results show that there is near-surface creep in the Laohushan segment of about 19 km. The locking degree changes significantly along the strike with the western part reaching 17 km and the eastern part of 3–7 km. The long-term slip rate gradually decreases from west 4.7 mm/yr to east 2.0 mm/yr. As such, there is large strain accumulation along the western part of the fault and shallow creep along the Laohushan segment; while in the eastern section, the degree of strain accumulation is low, which suggests the rupture segments of the 1920 earthquake may have been not completely relocked.